1999
DOI: 10.1007/s004100050578
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and H 2 O loss from fluid inclusions in natural quartz crystals

Abstract: Petrographic observations on quartz crystals from the Mole Granite (Australia) and other localities shed new light on the mechanisms of post-entrapment modification of fluid inclusions. These modifications include migration away from pseudosecondary trails, changes in fluid salinity and density, shape distortion and the formation of "sweat-haloes" around strongly deformed inclusions. Increases in fluid salinity, which usually are associated with inclusion migration, indicate water-losses of up to 50%. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(53 citation statements)
references
References 30 publications
0
53
0
Order By: Relevance
“…Audétat and Günther (1999) demonstrated that postentrapment modification of magmatic-hydrothermal fluid inclusions mostly led to loss of H 2 O, changing microthermometric properties (salinity, homogenisation behaviour). The metal ratios, however, remain largely unaffected except for Li.…”
Section: Post-entrapment Modification Of Fluid Inclusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Audétat and Günther (1999) demonstrated that postentrapment modification of magmatic-hydrothermal fluid inclusions mostly led to loss of H 2 O, changing microthermometric properties (salinity, homogenisation behaviour). The metal ratios, however, remain largely unaffected except for Li.…”
Section: Post-entrapment Modification Of Fluid Inclusionsmentioning
confidence: 99%
“…Post-entrapment modification of fluid inclusions may result either in changes in bulk fluid inclusion density without loss of content (stretching or shrinkage; Roedder 1984) or a gain or loss of material which may change both fluid inclusion composition and bulk density (e.g. Audétat and Günther 1999). The homogenisation of B2 MHBX brines from unambiguous boiling assemblages by final dissolution of halite, several tens of degrees Celsius above the temperature of bubble disappearance, indicates that such inclusions in the MHBX suffered from either volume shrinkage at constant salinity or selective water loss at constant inclusion volume, or both.…”
Section: Post-entrapment Modification Of Fluid Inclusionsmentioning
confidence: 99%
“…However, since it is not associated with a change in major element composition, H 2 O could be lost from inclusions via proton diffusion. This is a particularly feasible process for slow cooling of inclusions in intrusive rocks (Audetat and Gunther 1999). Figure 14 shows a melt inclusion in K-feldspar.…”
Section: Melt and Crystal Inclusion Studymentioning
confidence: 99%
“…The experiments illustrate that H 2 O can also diffuse against specific H 2 O fugacity gradients, and this process can be characterized as a crystal-recovery process, in which the included fluid is expelled from the crystal through migration of fluid pockets away from the inclusion. The results of this crystal-recovery process have been described in only a few studies on re-equilibration of fluid inclusions, both natural and synthetic [5,[26][27][28][29], whereas other work revealed only textural evidence of the occurrence of this process [6]. A direct consequence of this process would be the formation of a halo of relatively small H 2 O-rich inclusions around the original larger fluid inclusion and the recrystallization and inward growth of inclusion walls into a highly irregular pattern.…”
Section: Preferential H 2 O Lossmentioning
confidence: 99%